2019
DOI: 10.1556/606.2019.14.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the cooling energy consumption by the passive traditional façade strategies in hot dry climate

Abstract: The building façade becomes an integral part of the concept for adaptation of the building to the climate conditions; it should be able to respond and adapt its properties and components with the immediate environment.In the hot and dry climate in Algeria, the contemporary building design, materials, and techniques applied do not properly address the local climate conditions and the final energy consumption. Contrary to this, in traditional building practice, the local materials and passive strategies are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Façade design include the opening pattern, Windows configurations, type of glazing the that allows the lighting transmission and allow visual communication with outdoors for the occupants of the building and effects the visual comfort [22]. Designing and detailing the elevations of stone buildings in Jordan is not only functional; it can also be described as a purposeful act of ornamentation.…”
Section: Façade Designmentioning
confidence: 99%
“…Façade design include the opening pattern, Windows configurations, type of glazing the that allows the lighting transmission and allow visual communication with outdoors for the occupants of the building and effects the visual comfort [22]. Designing and detailing the elevations of stone buildings in Jordan is not only functional; it can also be described as a purposeful act of ornamentation.…”
Section: Façade Designmentioning
confidence: 99%
“…The use of some passive strategies, including the wind tower, the geothermal potential of the underground, and solar chimneys, can improve thermal comfort and energy consumption. Moreover, in some other cities in the south of Algeria, such as Biskra City [25][26][27] and Bousaada City [28], the impact of horizontal shading devices and materials on indoor comfort has been studied. In other countries, various studies on this topic have shown that thermal comfort may be improved by using passive building design.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis should be concluded by accounting for the interaction between natural lighting and the Heating, Ventilation and Air Conditioning (HVAC) system [10]. The amount of incident solar radiation (insolation) admitted through the glazed surfaces in the façade may show severe thermal and visual discomfort issues, in order to avoid excessive solar gain and reduce energy consumption it is necessary to adopt suitable shading device design [11]. The building façade design also plays an important role in providing effective ventilation configuration and strategies, in order to provide efficient Indoor Air Quality (IQA), which usually expressed by the CO 2 concentration in the space and the air ventilation rate [12].…”
Section: Introductionmentioning
confidence: 99%